Portable humidifier for refrigeration systems isolation room in a simple residential house - Ruhyat N.; Firdaus A. (BIO Web of Conferences)
Humans need fresh and clean air to live healthily. However, being in a dense and dense residential environment can potentially transmit diseases such as infections, bacteria, viruses, airborne microorganisms (airborne microorganisms), fungi, and other sources of infectious diseases. This is a concern in the air conditioning system. The air conditioning system regulates the air conditioning in the room to meet ideal conditions such as temperature and humidity. If you look at the Technical Guidelines for Buildings and Infrastructure Standards for Emerging Infectious Diseases (PIE) Isolation Rooms from the Ministry of Health of the Republic of Indonesia in 2020, at least the air temperature of residential rooms can reach an air temperature of 24 ± 20°C, with a relative humidity of 60%, so that fresh air is fulfilled. Experiments on portable humidifiers using single and double condensers from a refrigeration system provide design data on the need for air temperature and humidity for isolation rooms in simple residential houses. The standard temperature can be reached in a portable humidifier with a single condenser, namely 26-28°C. However, the humidity is still relatively high, at 80%, so bacteria can survive. However, when the air temperature in the lowest section (evaporator) is conditioned (10, 15, and 20°C), the air temperature exceeds the standard limit (39,38°C), even though the humidity is very low, reaching 34%. In experiments using a double condenser, the standard temperature and humidity can be said to be achieved; the temperature is 31°C, and the humidity is at 67%.